A randomized, double-blind, single-dose, single-center, parallel phase I clinical study comparing the pharmacokinetics, immunogenicity, safety, and tolerance of pertuzumab injection and Perjeta® in healthy Chinese male subjects. (1st February 2022) - Liu, Guangwen; Xu, Zhongnan; Yang, Wei; Xue, Jinling; Wang, Yanli; Liu, Zhengzhi; Cui, Yingzi; Qu, Xinyao; Chang, Tianying; Yu, Shuang; Cheng, Yang; Zhou, Yannan; et al.
Abstract: Background: Perjeta® is a recombinant, humanized monoclonal antibody that has been marketed and approved for the targeted therapy of human epidermal growth factor receptor (HER2) positive breast cancer in the United States. This study compared the bioequivalence, immunogenicity, and safety of pertuzumab injection (a biosimilar of Perjeta® produced by Chia Tai Tianqing Pharmaceutical Group Co., Ltd) and Perjeta® (produced by Roche Pharma AG) in healthy Chinese males. Research design and methods: Healthy Chinese male subjects (N = 87) were randomly given intravenous injection of 5 mg/kg pertuzumab or Perjeta® at a 1:1 ratio. Plasma drug concentrations were detected by enzyme-linked immunosorbent assay, and primary pharmacokinetic parameters were statistically analyzed. We detected the levels of anti-drug antibody (ADA) and neutralizing antibody (nAb) to evaluate drug immunogenicity and safety of the drugs throughout the study. Results: The geometric mean ratios of AUC0-t, Cmax, and AUC0-∞ for pertuzumab and Perjeta® were 100.42%, 96.71%, and 101.47%, respectively. The 90% CIs were all within 80%–125%, meeting the bioequivalence standards. The levels of ADA and nAb were similar. In addition, both had good safety in the study. Conclusion: The study shows that pertuzumab injection and Perjeta® had similar bioequivalence, immunogenicity, and safety.